Kematangan Emosi Ditinjau Dari Ketrampilan Problem Solving Pengurus OSIS SMAN 1 Colomadu Karanganyar - Rejeki, Nana Wahyu Sri; Putro, Eko Adi; Prihastari, Ema Butsi; Kamila, Sayida; Zainah, Siti (Universitas Mathla'ul Anwar Banten, 2025)
Intra-School Student Organization (OSIS) is the sole official organization within schools. This organization plays a role in encouraging students to actively contribute to school activities. It serves as a platform for student development, aiming to nurture students' interests, talents, and potential. OSIS has an organizational structure consisting of the OSIS advisor, OSIS board members, and OSIS members. As an intra-school organization, the OSIS board carries significant responsibility in managing student activities, fostering a positive atmosphere, and setting an example for other students. To carry out these responsibilities effectively, OSIS board members need to possess a high level of emotional maturity, which is reflected in their ability to manage emotions, show empathy, and solve problems wisely. At SMAN 1 Colomadu, the OSIS board plays a crucial role in creating a conducive and productive school environment. As OSIS board members, students are required to have a sense of responsibility, leadership, communication skills, and problem-solving abilities. The purpose of this study is to determine the level of emotional maturity and problem-solving skills possessed by the OSIS board members at SMAN 1 Colomadu. This research uses a qualitative approach through a systematic literature review, contextual analysis, and interviews. Interview data is analyzed using thematic analysis, where the researcher identifies patterns and relevant themes from the interview transcripts. The research results show that emotional maturity and problem-solving skills are two crucial aspects of OSIS leadership. The OSIS board members at SMAN 1 Colomadu Karanganyar have shown positive development, but there is still a need for improvement through continuous guidance and direct practice in real-life situations. By strengthening these two aspects, the performance of OSIS can become more effective and innovative.